JCO clinical cancer informatics: an American Society of Clinical Oncology journal (American Society of Clinical Oncology, 2017)
JCO Clinical Cancer Informatics (JCO CCI) is an online-only interdisciplinary journal publishing clinically relevant research based on biomedical informatics methods and processes applied to cancer-related data, information, and images